Understanding Consumer Behaviour towards Green Apparel: A Study of Purchase Intention in Kathmandu (Pravaha, 2025)
This study investigates the determinants of  consumers’ purchase intention and behaviour toward green apparel by extending the Theory of Planned Behaviour (TPB). The research model integrates attitude, subjective norm, and perceived behavioural control, the core TPB constructs alongside environmental concern and environmental knowledge. Data were collected from 269 respondents in Kathmandu, providing insights into urban consumers’ attitudes toward sustainable clothing. The findings reveal that all five factors positively influence consumers’ intention to purchase green apparel. Moreover, green purchase intention significantly mediates the relationship between these antecedents and actual purchase behaviour. The study suggests that marketers should work on improving consumer attitudes, raising awareness about the environment, and building a strong brand image focused on sustainability. Policymakers should encourage eco-friendly behaviour by offering educational programs and incentives for green apparel production. Although the study provides valuable insights, it also has limitations, such as focusing on general apparel and not specific products. Future research could explore different product types and other factors affecting green purchases. Overall, the findings offer practical ideas to promote sustainable fashion in urban Nepa